A Few Pt Single Atoms Are Responsible for the Overall Co‐Catalytic Activity in Pt/TiO2 Photocatalytic H2 Generation - Qin, Shanshan; Denisov, Nikita; Will, Johannes; Kolarík, Jan; Spiecker, Erdmann; Schmuki, Patrik (Solar RRL, 2022)
The use of single atoms (SAs) has become a highly investigated topic in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. In the field of photocatalysis, Pt SAs on TiO2 have been reported to be a highly efficient co-catalyst in solar H2 production. Herein, the deposition of Pt SAs and nanoparticles on titania nanosheets is investigated. In particular, the Pt species responsible for the high co-catalytic activity using a cyanide leaching process is elucidated. It is shown that neither Pt0 species nor the majority of Pt SAs do significantly contribute to the co-catalytic activity of platinum on TiO2. In fact, >90% of the Pt of a standard deposition are non-active and can be removed by cyanide leaching without activity loss—as a consequence, the remaining Pt SAs amount to a remarkable turnover frequency of 4.87 × 105 h−1 for H2 evolution.<br

Critical factors for photoelectrochemical and photocatalytic H-2 evolution from gray anatase (001) nanosheets - Qin, Shanshan; Denisov, Nikita; Zhou, Xin; Zdražil, Lukáš; Fehn, Dominik; Hwang, Imgon; Bruns, Mark; Kim, Hyesung; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2022)
In recent years, the defect engineering of titania via reduction treatments has shown a high potential for enabling efficient and co-catalyst-free photocatalytic H-2 generation from methanol/water solutions. However, defect engineering simultaneously alters several properties of TiO2. Here, we use pristine (white) and hydrogenated (gray) anatase nanosheets with dominant (001) facets. By comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H-2 evolution, we show that the increased conductivity or broad visible light absorption of gray titania is not responsible for its increased activity. Instead, the true bottleneck is the hole transfer rate that is significantly accelerated while using gray instead of white modification. Moreover, the hole transfer reaction causes the accumulation of the reaction products in pure water, hindering the photocatalytic H-2 evolution over time. These combined factors explain the superior performance of gray titania over white titania in photoelectrochemical or photocatalytic water splitting.
CRIS-Team WoS Importer:2022-10-07

Enhanced Photocatalytic H2 Generation by Light-Induced Carbon Modification of TiO2 Nanotubes - Nasir, Amara; Tesler, Alexander; Mohajernia, Shiva; Qin, Shanshan; Schmuki, Patrik; Mazare, Anca Valentina; Yasin, Tariq (ChemistryOpen, 2023)
Titanium dioxide (TiO2) is the material of choice for photocatalytic and electrochemical applications owing to its outstanding physicochemical properties. However, its wide bandgap and relatively low conductivity limit its practical application. Modifying TiO2 with carbon species is a promising route to overcome these intrinsic complexities. In this work, we propose a facile method to modify TiO2 nanotubes (NTs) based on the remnant organic electrolyte retained inside the nanotubes after the anodization process, that is, without removing it by immersion in ethanol. Carbon-modified TiO2 NTs (C-TiO2 NTs) showed enhanced H2 evolution in photocatalysis under UV illumination in aqueous solutions. When the C-TiO2 NTs were subjected to UV light illumination, the carbon underwent modification, resulting in higher measured photocurrents in the tube layers. After UV illumination, the IPCE of the C-TiO2 NTs was 4.4-fold higher than that of the carbon-free TiO2 NTs.
CRIS-Team Scopus Importer:2023-12-22
Keywords: annealing; hydrogen evolution; organic electrolytes; photoelectrochemical water splitting; TiO

Establishing High Photocatalytic H-2 Evolution from Multiwalled Titanate Nanotubes - Yoo, Jeong Eun; Alshehri, Abdulmohsen Ali; Qin, Shanshan; Bawaked, Salem Mohamed; Mostafa, Mohamed Mokhtar M.; Katabathini, Narasimharao; Fehn, Dominik; Schmidt, Jochen; Mazare, Anca Valentina; Denisov, Nikita; Cha, Gi; Meyer, Karsten; et al. (ChemCatChem, 2020)
Black TiO2 in various forms has been investigated for numerous photochemical applications. In photocatalytic water splitting, "grey" titania forms have been reported to reach considerable H-2 generation rates without using a noble metal co-catalyst. Up to now, a variety of anatase powders or other morphologies has been investigated in grey and black forms. Here we describe that hydrothermal titanate/anatase nanotubes can show a strong noble metal free photocatalytic activity. For optimized "blackening" conditions, a drastically higher photocatalytic H-2 production can be obtained than for other nanoscale morphologies. This effect can further be improved with a very mild Pt doping that again shows a clearly stronger photocatalytic H-2 production than comparably loaded nanopowders.
CRIS-Team WoS Importer:2020-05-15

Facet-Control versus Co-Catalyst-Control in Photocatalytic H-2 Evolution from Anatase TiO2 Nanocrystals - Qin, Shanshan; Shui, Lancang; Osuagwu, Benedict; Denisov, Nikita; Tesler, Alexander; Schmuki, Patrik (ChemistryOpen, 2022)
Titanium dioxide (TiO2) and, in particular, its anatase polymorph, is widely studied for photocatalytic H-2 production. In the present work, we examine the importance of reactive facets of anatase crystallites on the photocatalytic H-2 evolution from aqueous methanol solutions. For this, we synthesized anatase TiO2 nanocrystals with a large amount of either 001 facets, that is, nanosheets, or 101 facets, that is, octahedral nanocubes, and examined their photocatalytic H-2 evolution and then repeated this procedure with samples where Pt co-catalyst is present on all facets. Octahedral nanocubes with abundant 101 facets produce >4 times more H-2 than nanosheets enriched in 001 facets if the reaction is carried out under co-catalyst-free conditions. For samples that carry Pt co-catalyst on both 001 and 101 facets, faceting loses entirely its significance. This demonstrates that the beneficial role of faceting, namely the introduction of 101 facets that act as electron transfer mediator is relevant only for co-catalyst-free TiO2 surfaces.
CRIS-Team WoS Importer:2022-02-11

Fiber-Shaped Triboiontronic Electrochemical Transistor - Yu, Jinran; Qin, Shanshan; Zhang, Huai; Wei, Yichen; Zhu, Xiaoxiao; Yang, Ya; Sun, Qijun (Research, 2021)
Contact electrification-activated triboelectric potential offers an efficient route to tuning the transport properties in semiconductor devices through electrolyte dielectrics, i.e., triboiontronics. Organic electrochemical transistors (OECTs) make more effective use of ion injection in the electrolyte dielectrics by changing the doping state of the semiconductor channel. However, the mainstream flexible/wearable electronics and OECT-based devices are usually modulated by electrical signals and constructed in conventional geometry, which lack direct and efficient interaction between the external environment and functional electronic devices. Here, we demonstrate a fiber-shaped triboiontronic electrochemical transistor with good electrical performances, including a current on/off ratio as high as approximate to 1286 with off-current at similar to nA level, the average threshold displacements (D-th) of 0.3 mm, the subthreshold swing corresponding to displacement (SSD) at 1.6 mm/dec, and excellent flexibility and durability. The proposed triboiontronic electrochemical transistor has great potential to be used in flexible, functional, and smart self-powered electronic textile.
CRIS-Team WoS Importer:2021-05-21

Grey facet-controlled anatase nanosheets for photocatalytic H2 evolution without co-catalyst - Qin, Shanshan; Kim, Hyesung; Denisov, Nikita; Fehn, Dominik; Schmidt, Jochen; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2020)
Recently, black and grey titania in various morphologies have been intensively investigated for their high performance in photocatalytic H2 generation. Here we use titania nanosheets with a large percentage of (001) facets and hydrogenate them to activate suitable Ti3+-Ov defects for co-catalyst free H2 generation. Key to a highly active nanosheet-catalyst is the prevention of serious deformation and sintering during the thermal hydrogenation. In this work, we present a systematic investigation of different thermally treated nanosheets characterized by SEM, HR-TEM, TEM-EDX, XRD, EPR, XPS, and photocatalytic H2 evolution performance. We describe how to achieve robust grey nanosheets with an intact two-dimensional shape that can endure hydrogenation at the required high temperatures. Due to a defined faceting, these optimized "grey" nanosheets can produce photocatalytic H2 at a higher rate than previously reported best performing grey nanoparticles – this in spite of having a lower BET than the reduced nanoparticles.<br

Light‐induced agglomeration of single‐atom platinum in photocatalysis - Denisov, Nikita; Qin, Shanshan; Will, Johannes; Vasiljevic, Bojana Nedić; Skorodumova, Natalia V.; Pašti, Igor A.; Sarma, Bidyut Bikash; Osuagwu, Benedict; Yokosawa, Tadahiro; Voß, Johannes; Wirth, Janis; Spiecker, Erdmann; et al. (Advanced Materials, 2022)
With recent advances in the field of single-atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co-catalysts has been achieved. However, the stability and agglomeration of SA co-catalysts on the semiconductor surface may represent a critical issue in potential applications. Here we describe the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and finally nanoparticles takes place. The kinetics critically depends on the presence of sacrificial hole scavengers and the used light intensity. DFT calculations attribute the light induced destabilization of the SA Pt species to binding of surface-coordinated Pt with solution-hydrogen (adsorbed H atoms), which consequently weakens the Pt SA bonding to the TiO2 surface. Despite the gradual aggregation of Pt SAs into surface clusters and their overall reduction to metallic state, which involves >90% of Pt SAs, the overall photocatalytic H2 evolution remains virtually unaffected.<br

Light-Induced Migration of Spin Defects in TiO2 Nanosystems and their Contribution to the H2 Evolution Catalysis from Water - Bad'Ura, Zdenek; Naldoni, Alberto; Qin, Shanshan; Bakandritsos, Aristides; Kment, Stepan; Schmuki, Patrik; Zoppellaro, Giorgio (Chemsuschem, 2021)
The photocatalytic activity for H2 production from water, without presence of hole scavengers, of thermally reduced TiO2 nanoparticles (H-500, H-700) and neat anatase were followed by in-situ continuous-wave light-induced electron paramagnetic resonance technique (CW-LEPR), in order to correlate the H2 evolution rates with the electronic fingerprints of the photoexcited systems. Under UV irradiation, photoexcited electrons moved from the deep lattice towards the superficially exposed Ti sites. These photogenerated redox sites mediated (e−+h+) recombination and were the crucial electronic factor affecting catalysis. In the best-performant system (H-500), a synergic combination of mobile electrons was observed, which dynamically created diverse types of Ti3+ sites, including interstitial Ti3+, and singly ionized electrons trapped in oxygen vacancies (VO.). The interplay of these species fed successfully surface exposed Ti4+ sites, which became a catalytically active, fast reacting Ti4+⇄Ti3+ state that was key for the H2 evolution process.
CRIS-Team Scopus Importer:2021-09-10
Keywords: EPR spectroscopy; H; photocatalysis; titanium dioxide; water splitting

Metastable Ni(I)-TiO2-x Photocatalysts: Self-Amplifying H2 Evolution from Plain Water without Noble Metal Co-Catalyst and Sacrificial Agent - Altomare, Marco; Qin, Shanshan; Saveleva, Viktoriia A.; Badura, Zdenek; Tomanec, Ondrej; Mazare, Anca Valentina; Zoppellaro, Giorgio; Vertova, Alberto; Taglietti, Angelo; Minguzzi, Alessandro; Ghigna, Paolo; Schmuki, Patrik (Journal of the American Chemical Society, 2023)
Decoration of semiconductor photocatalysts with cocatalysts is generally done by a step-by-step assembly process. Here, we describe the self-assembling and self-activating nature of a photocatalytic system that forms under illumination of reduced anatase TiO2 nanoparticles in an aqueous Ni2+ solution. UV illumination creates in situ a Ni+/TiO2/Ti3+ photocatalyst that self-activates and, over time, produces H2 at a higher rate. In situ X-ray absorption spectroscopy and electron paramagnetic resonance spectroscopy show that key to self-assembly and self-activation is the light-induced formation of defects in the semiconductor, which enables the formation of monovalent nickel (Ni+) surface states. Metallic nickel states, i.e., Ni0, do not form under the dark (resting state) or under illumination (active state). Once the catalyst is assembled, the Ni+ surface states act as electron relay for electron transfer to form H2 from water, in the absence of sacrificial species or noble metal cocatalysts.
CRIS-Team Scopus Importer:2023-12-15

Minuscule Amounts of Pt Single Atoms Selectively Loaded on Minor (101) Facet of Anatase Crystallites Enables Outstanding Utilization Efficiency for Photocatalytic H2 Production - Qin, Shanshan; Denisov, Nikita; Osuagwu, Benedict; Kolařík, Jan; Sarma, Bidyut Bikash; Baďura, Zdeněk; Schmuki, Patrik (Advanced Functional Materials, 2025)
Pt single atoms (SAs) on TiO2 have been identified as effective co-catalysts in solar photocatalytic H2 production. In this study, Pt SAs is deposited on single crystal anatase nanosheets (NSs) with minor (101) and major (001) facets and expose them to various thermal treatments in air, Ar, and Ar-H2 environments. It is found that through Ar-H2 annealing Pt-species can be accumulated exclusively on the minor (101) facets, i.e., they can be concentrated selectively on the facet where electron exit occurs. This optimally establishes a high photocatalytic H2 evolution efficiency for an extremely low overall Pt SA loading of ≈0.005 wt.% on the anatase crystallites. For this most active SA placement, 11.7 mmol g−1 h−1 H2 production is obtained with a turnover frequency (TOF) up to 253 #H2 site−1 s−1. Note that the corresponding Pt SAs density of 3.1 × 104 atoms µm−2 is established by loading from only 0.2 µm Pt solution. These findings demonstrate that placing a very low density of Pt SAs as an electron transfer co-catalyst onto the electron exit sites of a light-harvesting structure (i.e., there where it is needed) can provide a most active photocatalytic structure with an outstanding Pt utilization.
CRIS-Team Scopus Importer:2025-02-14
Keywords: hydrogen evolution; photocatalysis; platinum; single-atom catalysts; TiO

Optimized Pt Single Atom Harvesting on TiO2 Nanotubes—Towards a Most Efficient Photocatalyst - Wu, Zhenni; Hwang, Imgon; Cha, Gi; Qin, Shanshan; Tomanec, Ondřej; Badura, Zdenek; Kment, Stepan; Zboril, Radek; Schmuki, Patrik (Small, 2021)
In the present work the authors show that anodic TiO2 nanotubes (NT) show excellent harvesting properties for Pt single atoms (Pt SAs) from highly dilute Pt solutions. The tube walls of anodic nanotubes, after adequate annealing to anatase, provide ample of suitable trapping sites—that is, surface Ti3+-Ov (Ov: oxygen vacancy) defects that are highly effective to extract and accumulate Pt in the form of SAs. A saturated (maximized) SA density can be achieved by an overnight immersion of a TiO2 NT layer to a H2PtCl6 solution with a concentration that is as low as 0.01 mm Pt. Such TiO2 NTs with surface trapped Pt SAs provide a maximized high activity for photocatalytic H2 generation (reaching a turnover frequency (TOF) of 1.24 × 106 h−1 at a density of 1.4 × 105 Pt atoms µm−2)—a higher loading with Pt nanoparticles does not further increase the photocatalytic activity. Overall, these findings show that anodic TiO2 nanotubes provide a remarkable substrate for Pt extraction and recovery from very dilute solutions that directly results in a highly efficient photocatalyst, fabricated by a simple immersion technique.
CRIS-Team Scopus Importer:2021-11-12
Keywords: dark deposition; hydrogen generation; photocatalysis; single-atom catalysis; TiO

Pd single atoms on g-C3N4 photocatalysts: minimum loading for maximum activity - Velu, Jeyalakshmi; Wu, Siming; Qin, Shanshan; Zhou, Xin; Sarma, Bidyut Bikash; Doronkin, Dimitry E.; Kolařík, Jan; Šoóš, Miroslav; Schmuki, Patrik (Chemical Science, 2025)
Noble metal single atoms (SAs) on semiconductors are increasingly explored as co-catalysts to enhance the efficiency of photocatalytic hydrogen production. In this study, we introduce a “spontaneous deposition” approach to anchor Pd SAs onto graphitic carbon nitride (g-C3N4) using a highly dilute tetraaminepalladium(ii) chloride precursor. Maximized photocatalytic activity and significantly reduced charge transfer resistance can be achieved with a remarkably low Pd loading of 0.05 wt% using this approach. The resulting Pd SA-modified g-C3N4 demonstrates a remarkable hydrogen production efficiency of 0.24 mmol h−1 mg−1 Pd, which is >50 times larger than that of Pd nanoparticles deposited on g-C3N4via conventional photodeposition. This significant enhancement in catalytic performance is attributed to improved electron transfer facilitated by the optimal coordination of Pd SAs within the g-C3N4 structure.
CRIS-Team Scopus Importer:2025-02-28

Photocatalytic H2 Generation: Controlled and Optimized Dispersion of Single Atom Co-Catalysts Based on Pt-TCPP Planar Adsorption on TiO2 - Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
When using single atoms (SAs) as a co-catalyst in photocatalytic H2 generation, achieving a well-dispersed, evenly distributed and adjustable SA surface density on a semiconductor surface is a challenging task. In the present work we use the planar adsorption of tetrakis-(4-carboxyphenyl)-porphyrin (TCPP) and its platinum coordinated analogue, Pt-TCPP, onto anatase TiO2 surfaces to establish a spatially controlled decoration of SAs. We show that the surface Pt SA density can be very well controlled by co-adsorption of Pt-TCPP and TCPP in the planar monolayer regime, and by adjusting the Pt-TCPP to TCPP ratio a desired well dispersed surface density of SAs up to 2.6×105 atoms μm−2 can be established (which is the most effective Pt SA loading for photocatalysis). This distribution and the SA state are maintained after a thermal treatment in air, and an optimized SA density as well as a most active form of Pt for photocatalytic H2 evolution can be established and maintained.
CRIS-Team Scopus Importer:2024-02-16
Keywords: hydrogen evolution; photocatalysis; platinum; porphyrins; single-atom catalysts

Photocatalytic Hydrogen Generation from Water-Annealed TiO2 Nanotubes with White and Grey Modification - Fu, Fan; Cha, Gi; Wu, Zhenni; Qin, Shanshan; Zhang, Yan; Chen, Yuyue; Schmuki, Patrik (ChemElectroChem, 2021)
In recent years, photocatalytic reactions on anodic TiO2 nanotubes have been intensively investigated. In order to show photocatalytic activity, anodically formed nanotubes need to be crystallized to anatase. This is conventionally done by thermal annealing in air at temperatures 400–600 °C. Recently, a so-called “water annealing” treatment has been reported to be effective to also create a highly active form for photocatalysis. Here we report on the feasibility of using a water annealing treatment of TiO2 nanotubes to create a photocatalyst for H2 production that is as active as conventional thermal annealing. If the water-annealed samples are additionally hydrogenated to a so-called “grey” modification, a further significant improvement of the photocatalytic activity for H2 evolution can be achieved – this without the use of any noble metal co-catalyst. A combination of water annealing, thermal annealing, followed by hydrogenation can deliver a H2 generation activity that is more than five times higher than that achieved by thermal annealing of anodic TiO2 nanotubes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: hydrogenation; optimized water annealing; TiO; titanium (III); water splitting

Photocatalytic Synthesis of Oxidized Graphite Enabled by Grey TiO2 and Direct Formation of a Visible-Light-Active Titania/Graphene Oxide Nanocomposite - Nasir, Amara; Mazare, Anca Valentina; Zhou, Xin; Qin, Shanshan; Denisov, Nikita; Zdrazil, Lukas; Kment, Stepan; Zboril, Radek; Yasin, Tariq; Schmuki, Patrik (Chemphotochem, 2022)
Herein we report a one-step, low cost, photocatalytic method for the synthesis of graphene oxide (GO) from commercial graphite using grey TiO2 as a photocatalyst. GO formation is achieved by UV-illumination of a slurry of well-dispersed grey TiO2 and commercial graphite. Light-induced valence-band holes from grey TiO2 then lead to an oxidation and exfoliation of graphite, resulting in the formation of visible-light-active GO. An optimal level of graphite oxidation can be established by controlling the UV illumination time. Moreover, the resulting GO-decorated TiO2 is directly active as a visible-light-active photocatalyst that can, for example, be used for pollution degradation.
CRIS-Team Scopus Importer:2022-04-15
Keywords: graphene oxide; graphite; grey TiO; methylene-blue degradation; UV illumination

Photoelectrochemical properties of “increasingly dark” TiO2 nanotube arrays - Denisov, Nikita; Qin, Shanshan; Cha, Gi; Yoo, Jeong Eun; Schmuki, Patrik (Journal of Electroanalytical Chemistry, 2020)
“Black” TiO2 nanotube arrays (TNTAs) of different darkness are formed by thermal reduction of anodic TiO2 nanotube layers in H2 atmosphere at different temperatures (300–500 °C), and their (photo-)electrochemical properties are studied by IPCE spectroscopy, transient photocurrent measurements, IMPS, PEIS, CV, and Mott-Schottky analysis. Hydrogenation of the TNTAs leads to the enhancement of their IPCE (by up to 1.5 times), despite increased recombination losses at anodic potentials. Reduced TNTAs demonstrate a “metallic” behavior by a characteristic frequency response of their impedance and phase angle, reduced charge transfer resistance at anodic bias, increased double layer capacitance, and remarkably increased donor densities (up to 7.25 × 1023 cm−3). The observed alterations in the properties of TNTAs after hydrogenation are ascribed to the formation of defects and TiHx.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Anodization; Black titania; Hydrogenation; Nanotubes; Photoelectrochemistry; TiO

Pt-single atom decorated TiO2: Tuning anodic TiO2 nanotube structure and geometry toward a high-performance photocatalytic H2 production - Chen, Xuewen; Qin, Shanshan; Denisov, Nikita; Kure-Chu, Song Zhu; Schmuki, Patrik (Electrochimica Acta, 2023)
Atomically dispersed Pt single atoms (SAs) on titania have been reported to be a highly effective co-catalyst in photocatalytic H2 generation. In this report, we grew layers of anodic TiO2 nanotubes (NTs) varying the lengths of the NTs from 1 to 18 μm as well as their crystalline state by thermal annealing over a wide range of temperatures (350 °C – 800 °C). We then decorated the nanotubes with single atom (SA) Pt co-catalysts deposited from H2PtCl6 solutions with various concentrations of 0.001–2 mM Pt and evaluate the photocatalytic H2 generation performance for the different NT layers under UV and solar illumination. The highest photocatalytic performance is achieved for 15–18 μm long anatase NTs decorated with Pt SAs from a 0.01 mM H2PtCl6 solution (leading to a Pt SA surface concentration of 5.6 × 105 /µm2). Except for a sufficient SA Pt loading and an anatase structure, the key parameter is the photon absorption length for near-band-gap UV and AM 1.5 light. Such optimized Pt SA@TiO2 NTs show a most efficient H2, outperforming many other photocatalytic 3D titania structures, such as titania-based powders, flakes, and Metal–Organic Frameworks (MOFs) tested under the same illumination conditions.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Photocatalytic H; Pt single atoms; TiO; TiO; TiO

Pt single atoms dispersed in a hybrid MOFox-in-nanotube structure for efficient and long-term stable photocatalytic H2 generation - Qin, Shanshan; Guo, Junli; Chen, Xuewen; Cao, Ran; Denisov, Nikita; Song, Yan Yan; Schmuki, Patrik (Journal of Materials Chemistry A, 2023)
Atomically dispersed Pt single atoms (SAs) have been reported to be a highly effective co-catalyst on TiO2 for photocatalytic H2 generation. Many TiO2 supports have been explored for hosting Pt SAs. Particularly 1D titania hosts allow for an optimized light and charge carrier management. But, attached Pt SAs often suffer from agglomeration during the photocatalytic process. In this context, titania-based metal-organic frameworks (MOFs), such as MIL-125, have attracted wide attention, as they provide stable anchoring sites for Pt SAs. To combine the beneficial features of the 1D TiO2 morphology with the SA stability, we introduce here a hierarchical structure, where the Pt SAs are dispersed in MOF-derived porous oxide features that are embedded in aligned anodic TiO2 nanotubes. This hybrid structure is intrinsically (within the nanotubes) synthesized and combines the excellent light harvesting and carrier transport properties of titania nanotubes with the beneficial features of MOF. As a result of this synergy, we obtain not only a high photocatalytic H2 evolution efficiency but most importantly a remarkably long-term stability of H2 evolution under UV light (365 nm) or simulated solar light (AM 1.5).
CRIS-Team Scopus Importer:2023-09-15

Pt Single Atoms on TiO2 Polymorphs-Minimum Loading with a Maximized Photocatalytic Efficiency - Qin, Shanshan; Denisov, Nikita; Sarma, Bidyut Bikash; Hwang, Imgon; Doronkin, Dmitry E.; Tomanec, Ondrej; Kment, Stepan; Schmuki, Patrik (Advanced Materials Interfaces, 2022)
For more than 20 years, Pt/TiO2 represents the benchmark photocatalyst/co-catalyst platform for photocatalytic hydrogen (H-2) generation. Here, single atom (SA) Pt is decorated on different polymorphs of TiO2 (anatase, rutile, and the mixed phase of P25) using a simple immersion anchoring approach. On P25 and anatase, Pt SAs act as highly effective co-catalyst for pure water splitting with a photocatalytic H-2 evolution activity (4600 mu mol h(-1) g(-1))-on both polymorphs, SA deposition yields a significantly more active photocatalyst than those decorated with classic Pt nanoparticles or conventional SA deposition approaches. On rutile, Pt SAs provide hardly any co-catalytic effect. Most remarkable, for P25, the loading of Pt SAs from precursor solution with a very low concentration (<1 ppm Pt) leads already to a maximized co-catalytic effect. This optimized efficiency is obtained at 5.3 x 10(5) atoms mu m(-2) (at macroscopic loading of 0.06 at%)-for a higher concentration of Pt (a higher density of SAs), the co-catalytic efficiency is significantly reduced due to H-2/O-2 recombination. The interactions of the SA Pt with the different polymorphs that lead to this high co-catalytic activity of SA Pt at such low concentrations are further discussed.
CRIS-Team WoS Importer:2022-07-08
Keywords: diffuse reflectance infra-red spectroscopy; photocatalytic H 2 evolution photoluminescence; Pt single atoms; TiO 2 polymorphs; X-ray absorption fine structure; X-ray absorption near-edge spectra

Reactive deposition of Pt single-atoms on g-C3N4: effect of Pt-precursors - Lazaar, Nawres; Qin, Shanshan; Hamrouni, Abdessalem; Lachheb, Hinda; Kolařík, Jan; Zhou, Xuemei; Schmuki, Patrik (Nanoscale, 2025)
Anchoring Pt single atoms (SAs) as co-catalysts on g-C3N4 has emerged as a promising approach to enhance the hydrogen production performance of this photocatalytic system. Particularly, by so-called reactive deposition, a maximum hydrogen evolution reaction performance can be achieved using a minimum amount of Pt loading. In this study, we explore the effects of different platinum (Pt) precursors on the reactive deposition of SAs onto g-C3N4, aiming to optimize the performance in photocatalytic hydrogen production. By examining a variety of Pt precursor types, we highlight critical parameters influencing deposition, including precursor charge, solution pH, ionic strength, and ligand properties. Our results reveal that precursors bearing anionic charges are distinctly more effective than cationic precursors for depositing highly active Pt SAs. Crucially, we find that the surface deposition reaction strongly depends on the ligand involved, with chloride-based complexes enabling more efficient Pt attachment compared to bromide-based complexes. Notably, variations in the oxidation state of platinum (Pt4+ versus Pt2+) did not significantly influence deposition outcomes. Among all precursors studied, (NH4)2[PtCl6] achieved the highest catalytic activity, with optimal Pt loading (∼0.026 wt%) and superior hydrogen evolution rates surpassing the widely utilized H2[PtCl6] precursor. Furthermore, adjustments to solution conditions, such as significant pH changes due to increased ionic strength, were found to negatively impact deposition and catalytic effectiveness. These insights underscore the importance of precursor selection and solution chemistry control, providing a robust basis for the development of efficient and cost-effective single-atom photocatalysts formed by adsorption–reaction treatments.
CRIS-Team Scopus Importer:2025-10-24

Reactive Deposition Versus Strong Electrostatic Adsorption (SEA): A Key to Highly Active Single Atom Co-Catalysts in Photocatalytic H2 Generation - Wang, Yue; Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Bad'ura, Zdeněk; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced Materials, 2023)
In recent years, the use of single atoms (SAs) has become of a rapidly increasing significance in photocatalytic H2 generation; here SA noble metals (mainly Pt SAs) can act as highly effective co-catalysts. The classic strategy to decorate oxide semiconductor surfaces with maximally dispersed SAs relies on “strong electrostatic adsorption” (SEA) of suitable noble metal complexes. In the case of TiO2 – the classic benchmark photocatalyst – SEA calls for adsorption of cationic Pt complexes such as [(NH3)4Pt]2+ which then are thermally reacted to surface-bound SAs. While SEA is widely used in literature, in the present work it is shown by a direct comparison that reactive attachment based on the reductive anchoring of SAs, e.g., from hexachloroplatinic(IV) acid (H2PtCl6) leads directly to SAs in a configuration with a significantly higher specific activity than SAs deposited with SEA – and this at a significantly lower Pt loading and without any thermal post-deposition treatments. Overall, the work demonstrates that the reactive deposition strategy is superior to the classic SEA concept as it provides a direct electronically well-connected SA-anchoring and thus leads to highly active single-atom sites in photocatalysis.
CRIS-Team Scopus Importer:2023-08-18
Keywords: highly reactive single-atom deposition; photocatalytic H; Pt co-catalysts; sputtered anatase layers

Reduced Grey Brookite for Noble Metal Free Photocatalytic H2 Evolution - Wierzbicka, Ewa; Altomare, Marco; Wu, Mingjian; Liu, Ning; Yokosawa, Tadahiro; Fehn, Dominik; Qin, Shanshan; Meyer, Karsten; Unruh, Tobias; Spiecker, Erdmann; Palmisano, Leonardo; Bellardita, Marianna; et al. (Journal of Materials Chemistry A, 2020)
Herein we introduce for the first time a reduced “grey” brookite TiO2 photocatalyst, produced by thermal hydrogenation of brookite nanoparticles, that shows a remarkable noble metal free photocatalytic H2 evolution. Its activity is substantially higher than that of other TiO2 polymorphs, i.e. anatase or rutile, comparably sized and activated by hydrogenation under optimized conditions. Along with brookite powders, an oriented brookite single crystal was investigated as a defined surface to confirm the effects of the hydrogenation treatment. By a combination of Electron paramagnetic resonance (EPR), electron and X-ray characterization techniques applied to the powders and single crystal, we find that hydrogenation forms in brookite a defective crystalline surface layer rich in Ti3+ states. Amorphization effects, i.e. forming the so called “amorphous shell” as reported in previous work for black anatase TiO2, were not detected. Overall, we provide experimental evidence that hydrogenation forms in brookite a surface strained zone with point defects that are mediators for electron transfer to H2O, leading to a significantly enhanced noble metal free photocatalytic H2 evolution in comparison to anatase.<br

Self-assembly of a Ni(I)-photocatalyst for plain water splitting without sacrificial agents - Qin, Shanshan; Badura, Zdenek; Denisov, Nikita; Tomanec, Ondrej; Mohajernia, Shiva; Liu, Ning; Kment, Stepan; Zoppellaro, Giorgio; Schmuki, Patrik (Electrochemistry Communications, 2021)
The present work describes a self-assembling photocatalytic system that is observed when illuminating grey titania nanoparticles in suspension with a plain aqueous Ni2+ solution. Such a suspension (in contrast to white titania), under UV illumination, increasingly produces H2 from neutral water. We show that the origin of this self-activation is not the light-induced deposition of Ni0 or another Ni-catalyst compound on the titania surface. Rather, in-situ electron paramagnetic resonance (EPR) clearly indicates that the activation is due to a light-induced formation of a suitable defect structure (Ti3+-OV) on grey titania, combined with the formation of an intermediate monovalent nickel (Ni(I)) electron transfer relay. Remarkably, the resulting Ni+/TiO2/Ti3+ photocatalyst operates in absence of any noble metal or sacrificial agent.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Hydrogen evolution; Hydrogenated anatase titania; Ni(I)-photocatalyst; Plain water splitting; Self-assembly

Silver-Loaded Titania-Based Metal–Organic Frameworks as a Platform for Silver Ion Release for Antibacterial Applications - Mazare, Anca Valentina; Goldmann, Wolfgang; Kocak, Esra; Osuagwu, Benedict; Qin, Shanshan; Cao, Ran; Schmuki, Patrik (Nano Letters, 2025)
Conventional Ag-decorated TiO2coatings suffer from low adsorption capacity and burst release kinetics, limiting long-term antibacterial efficacy and risking cytotoxicity. An entirely different payload release approach can be based on metal–organic frameworks (MOFs), which offer tunable porosity, high surface area, and internal diffusion channels. Here, we report a thermally stabilized Ti-based MOF [NH2-MIL-125(Ti)] functionalized with Ag+via reactive deposition, enabling high Ag loading (∼14.7 wt %) and sustained release. Annealing at 250 °C enhances aqueous stability, allowing diffusion-governed Ag+delivery over >48 h, with 77% of the Ag still present in the MOF after a 24 h release. The system exhibits dose-dependent antibacterial activity in powders and comparable efficacy in coatings, with a more gradual release profile. This scalable platform is promising for long-acting coatings, wound interfaces, and implantable materials.
CRIS-Team Scopus Importer:2025-08-29
Keywords: antibacterial activity; metal−organic-frameworks (MOFs); NH; silver

Single-Atom Catalysts on C3N4: Minimizing Single Atom Pt Loading for Maximized Photocatalytic Hydrogen Production Efficiency - Lazaar, Nawres; Wu, Siming; Qin, Shanshan; Hamrouni, Abdessalem; Bikash Sarma, Bidyut; Doronkin, Dimitry E.; Denisov, Nikita; Lachheb, Hinda; Schmuki, Patrik (Angewandte Chemie International Edition, 2025)
The use of metal single atoms (SAs) as co-catalysts on semiconductors has emerged as a promising technology to enhance their photocatalytic hydrogen production performance. In this study, we describe the deposition of very low amounts of Pt SAs (<0.1 at %) on exfoliated graphitic carbon nitride (C3N4) by a direct Pt−deposition approach from highly dilute chloroplatinic acid precursors. We find that − using this technique−a remarkably low loading of highly dispersed Pt SAs (0.03 wt %) on C3N4 is sufficient to achieve a drastic decrease in the overall charge transfer resistance and a maximized photocatalytic efficiency. The resulting low-loaded Pt SAs/C3N4 provides a H2 production rate of 1.66 m mol/h/mg Pt, with a remarkable stability against agglomeration; even during prolonged photocatalytic reactions no sign of light-induced Pt agglomerations can be observed. We ascribe the high performance and stability to the site-selective, stable coordination of Pt within the C3N4 structure. Notably the H2 production rate of the low-loaded Pt SAs surpasses the activity of Pt SAs deposited by other techniques or nanoparticles at comparable or even higher loading – the optimized Pt SAs decorated C3N4 show ≈5.9 times higher rate than Pt NP decorated C3N4.
CRIS-Team Scopus Importer:2025-01-31
Keywords: C; dark deposition; H; photocatalysis; Pt single atoms

Single Atoms in Photocatalysis: Low Loading Is Good Enough! - Qin, Shanshan; Will, Johannes; Kim, Hyesung; Denisov, Nikita; Carl, Simon; Spiecker, Erdmann; Schmuki, Patrik (ACS Energy Letters, 2023)
We disperse Pt single atoms (SAs) with different loading densities on anatase TiO2 thin films and evaluate the photocatalytic H2 generation as a function of the incident light intensity. We show that under common illumination intensities (such as terrestrial solar illumination), a minuscule Pt SA loading of ∼105 atoms μm-2 (surface Pt content ∼0.1 at.%) is sufficient to achieve a maximized H2 production rate. This results in a maximum turnover frequency at a single Pt atom site of ∼300 H2 molecules s-1. For a vast majority of illumination conditions and a suitable surface configuration, it is not the density of co-catalytic sites that is rate-determining (a high loading is not needed!), but the charge carrier generation (and flux of photoelectrons to the co-catalytic centers) determines the overall reaction rate. This is in stark contrast to SA catalysis of classic chemical reactions where generally a maximum loading of reactive SA delivers a maximum activity.
CRIS-Team Scopus Importer:2023-02-10

Stable and Highly Active Single Atom Configurations for Photocatalytic H2 Generation - Wang, Yue; Denisov, Nikita; Qin, Shanshan; Gonçalves, Danielle Santos; Kim, Hyesung; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced Materials, 2024)
The employment of single atoms (SAs), especially Pt SAs, as co-catalysts in photocatalytic H2 generation has gained significant attention due to their exceptional efficiency. However, a major challenge in their application is the light-induced agglomeration of these SAs into less active nanosized particles under photocatalytic conditions. This study addresses the stability and reactivity of Pt SAs on TiO2 surfaces by investigating various post-deposition annealing treatments in air, Ar, and Ar-H2 environments at different temperatures. It is described that annealing in an Ar-H2 atmosphere optimally stabilizes SA configurations, forming stable 2D rafts of assembled SAs ≈0.5–1 nm in diameter. These rafts not only resist light-induced agglomeration but also exhibit significantly enhanced H2 production efficiency. The findings reveal a promising approach to maintaining the high reactivity of Pt SAs while overcoming the critical challenge of their stability under photocatalytic conditions.
CRIS-Team Scopus Importer:2024-04-12
Keywords: photocatalytic H; Pt co-catalyst; single atom configurations; sputtered anatase layers

Thermally-induced agglomeration tailors the stability of Pt SAs on TiO2 and use in photocatalytic H2 generation - Will, Johannes; Denisov, Nikita; Qin, Shanshan; Wu, Mingjian; Wang, Yue; Kim, Hyesung; Karpstein, Nicolas; Dierner, Martin; Schmuki, Patrik; Spiecker, Erdmann (Journal of Materials Chemistry A, 2025)
Thermally-induced agglomeration of Pt single atoms (SAs) on anatase TiO2 thin films is exploited for tuning their activity in photocatalytic H2 generation. After thermal treatment at temperatures ranging from 350 to 650 °C in an Ar atmosphere, a more than fivefold higher photocatalytic activity is achieved under optimized conditions. The Pt species obtained after annealing at different temperatures are monitored via ex situ and in situ transmission electron microscopy. For in situ measurements, a gas cell system operating at 700 mbar is utilized. Structural data obtained in the temperature range from 250 to 950 °C demonstrate the co-existence of SA species and agglomerates over the whole temperature range, and give fundamental insights into thermal and light-induced agglomeration processes, including nucleation, growth and ripening of Pt species on TiO2. Under optimized annealing conditions Pt is present as a mixture of SAs, 2D rafts and nanoparticles. Data show that annealing can stabilize the Pt species against light-induced agglomeration and detailed analysis reveals such SAs (realized under optimized annealing conditions) provide the most active sites (in comparison with various agglomerates). We further emphasize the importance of conducting atomic-scale structural characterization both before and after photocatalysis to accurately establish the process-structure-property-performance relationships of SAs in photocatalysis.
CRIS-Team Scopus Importer:2025-04-11